2015
DOI: 10.1016/j.ic.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Upwards closed dependencies in team semantics

Abstract: We prove that adding upwards closed first-order dependency atoms to first-order logic with team semantics does not increase its expressive power (with respect to sentences), and that the same remains true if we also add constancy atoms. As a consequence, the negations of functional dependence, conditional independence, inclusion and exclusion atoms can all be added to first-order logic without increasing its expressive power.Furthermore, we define a class of bounded upwards closed dependencies and we prove tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…This, however, has not been answered yet. In [9], a very general family of dependencies was found that does not increase the expressive power of First Order Logic if added to it; but it is an open question whether any dependency that has this property is definable in terms of dependencies in that family (and, in fact, in this work we will show that this is false).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…This, however, has not been answered yet. In [9], a very general family of dependencies was found that does not increase the expressive power of First Order Logic if added to it; but it is an open question whether any dependency that has this property is definable in terms of dependencies in that family (and, in fact, in this work we will show that this is false).…”
Section: Introductionmentioning
confidence: 84%
“…It certainly is true that every Inclusion Logic sentence is equivalent to some Independence Logic sentence, that every Dependence Logic sentence is equivalent to some Independence Logic sentence, and that every Independence Logic sentence is equivalent to some Dependence Logic sentence; but on the other hand, it is not true that every Inclusion Logic formula, or every Independence Logic one, is equivalent to some Dependence Logic formula. This follows at once from the following classification: Definition 9 (Empty Team Property, Closure Properties - [29,8,9]) Let D be a generalized dependency. Then…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Notice that it might be impossible to define consistently the union of two causal teams 6. To the best of our knowledge, this connective has been used, with different notation, in[8], as a special case of the maximal implication introduced in[15].…”
mentioning
confidence: 99%